Terapi Sindrom Koroner Akut Fokus pada Revaskularisasi - Adri Adri; Aulia Mustika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Cardiovascular dysfunction is a disorder of the blood vessels, such as hypertension, heart failure, and stroke. In 2016, cardiovascular disease was the leading cause of death worldwide, based on data from the World Health Organization (WHO). Coronary Heart Disease (CHD) is the leading cause of death, along with stroke, as shown by the Sample Registration System survey in 2014.This case involves a 64-year-old male, Mr. N, who presented to the emergency department of RSUD dr. Fauziah Bireuen with complaints of chest pain that developed gradually and worsened over the past month. The pain was located across the entire chest and radiated to the back and neck. The pain was described as severe, like being crushed by a heavy load, worsened during strenuous activities such as cutting grass and chopping wood, and relieved when the patient bent forward. The pain could occur at any time, with a Visual Analog Scale (VAS) score of 10 (severe pain). The patient also reported easy fatigue during heavy physical activity over the past month. Laboratory examination revealed elevated leukocytes, mean corpuscular volume (MCV), segmented neutrophils, troponin I, cholesterol, and triglycerides. The patient was diagnosed with extensive anterior ST-elevation myocardial infarction (STEMI) post successful fibrinolytic therapy.